2018
DOI: 10.1029/2018jd028980
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of the Arctic Troposphere on the Midlatitude Climate Variability and the Recent Eurasian Cooling

Abstract: Understanding the influence of the Arctic troposphere on the climate at midlatitudes is critical for projecting the impacts of ongoing and anticipated Arctic changes such as Arctic amplification and rapid sea ice decline over the Northern Hemisphere. In this study, we analyze a suite of atmospheric model experiments, with and without atmospheric relaxation toward reanalysis data, to study the impacts of the Arctic troposphere on the midlatitude atmospheric circulation and climate variability. The Arctic tropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 64 publications
5
37
0
Order By: Relevance
“…It would be interesting to compare the relative strength of these "teleconnections" based on model relaxation experiments, complementing the observational analysis by Cohen (2016). In fact, the results of this study can be qualitatively compared to that of Jung et al (2014) and especially that of Ye et al (2018).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It would be interesting to compare the relative strength of these "teleconnections" based on model relaxation experiments, complementing the observational analysis by Cohen (2016). In fact, the results of this study can be qualitatively compared to that of Jung et al (2014) and especially that of Ye et al (2018).…”
Section: Discussionmentioning
confidence: 89%
“…Assuming linearity, the impacts of midlatitudes on the Arctic regions can be obtained by taking the differences between the two experiments (TropMidlat-Trop; see supporting information for further details). Similar analyses of relaxation experiments were carried out by Jung et al (2014) and Ye et al (2018), with the goal to study the impacts of the Arctic on midlatitude weather and climate. Two additional experiments without relaxation were run with climatological SST/SIC (CLIM SST,SI , reference experiment) and with observed SST/SIC conditions (OBS SST,SI ), respectively.…”
Section: Model Relaxation Experimentsmentioning
confidence: 98%
“…Supplemental information related to this paper is available at the Journals Online website: https://doi.org/10.1175/JCLI-D-19-0403.s1. blocking frequency over the Urals, Greenland, and Siberia (Luo et al 2016a;Ye et al 2018;Chen et al 2018). Additionally, anticyclone activity and the frequency of cold extremes over Eurasia have both intensified in recent years (e.g., Zhang et al 2008;Overland et al 2011;Zhang et al 2012;Cohen et al 2010Cohen et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Mori et al (2014) identified the WACE pattern as the second empirical orthogonal function (EOF) of SAT variability over the Arctic-Eurasian sector, excited directly by the sea ice decline over the BKS. Additional proposed mechanisms contributing to the WACE pattern include internal atmospheric variability (e.g., McCusker et al 2016;Sun et al 2016;Ogawa et al 2018), the poleward shift of the oceanic front in the Gulf Stream region (Sato et al 2014;Simmonds and Govekar 2014), anomalies in Eurasian snow cover (Xu et al 2018) and manifestations of independent phenomena that jointly contribute to an anomalous temperature dipole (Ye et al 2018). Others have analyzed the low-frequency variability in the WACE pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have started to look at such teleconnections from a prediction perspective, concluding that improved Arctic prediction will lead to improved predictions at daily-to-seasonal ranges, particularly over northern parts of America and Asia (Jung et al, 2014). Indeed, it is thought that the tropospheric circulation over north Asia is more closely tied to the circulation in the Arctic than the Tropics (Ye et al, 2018). This is thought to be because the mean stationary-wave structures in the Northern Hemisphere promote flow out of the Arctic into north Asia .…”
Section: Introductionmentioning
confidence: 99%